Migrating memories : Romanian Germans in modern Europe - Koranyi, James (2022)
"At some point in the twelfth century, a group of people went in search of a new homeland 'beyond the forest'. On their journey, they encountered aurochs still roaming freely and bears looking for honey. Eventually, they reached the land they were looking for: Transylvania. On arrival, two of the men drew their swords and rammed them into the ground, swearing allegiance to their new homeland. They then separated, each taking their sword to a different place: one to Broos (Orăştie) in western Transylvania, and the other to Draas (Drăuşeni) in eastern Transylvania, where the swords would remain as symbols of their attachment to the wonderous new land. The new settlers worked the land, enduring hardship and wars in the centuries that followed"